Oral Immunization with a Live Coxsackievirus/HIV Recombinant Induces Gag p24-Specific T Cell Responses - Gu, Rui (Public Library of Science, 2010)
BACKGROUND: The development of an HIV/AIDS vaccine has proven to be elusive. Because human vaccine trials have not yet demonstrated efficacy, new vaccine strategies are needed for the HIV vaccine pipeline. We have been developing a new HIV vaccine platform using a live enterovirus, coxsackievirus B4 (CVB4) vector. Enteroviruses are ideal candidates for development as a vaccine vector for oral delivery, because these viruses normally enter the body via the oral route and survive the acidic environment of the stomach. METHODOLOGY/PRINCIPAL FINDINGS: We constructed a live coxsackievirus B4 recombinant, CVB4/p24(73(3)), that expresses seventy-three amino acids of the gag p24 sequence (HXB2) and assessed T cell responses after immunization of mice. The CVB4 recombinant was physically stable, replication-competent, and genetically stable. Oral or intraperitoneal immunization with the recombinant resulted in strong systemic gag p24-specific T cell responses as determined by the IFN-γ ELISPOT assay and by multiparameter flow cytometry. Oral immunization with CVB4/p24(73(3)) resulted in a short-lived, localized infection of the gut without systemic spread. Because coxsackieviruses are ubiquitous in the human population, we also evaluated whether the recombinant was able to induce gag p24-specific T cell responses in mice pre-immunized with the CVB4 vector. We showed that oral immunization with CVB4/p24(73(3)) induced gag p24-specific immune responses in vector-immune mice. CONCLUSIONS/SIGNIFICANCE: The CVB4/p24(73(3)) recombinant retained the physical and biological characteristics of the parental CVB4 vector. Oral immunization with the CVB4 recombinant was safe and resulted in the induction of systemic HIV-specific T cell responses. Furthermore, pre-existing vector immunity did not preclude the development of gag p24-specific T cell responses. As the search continues for new vaccine strategies, the present study suggests that live CVB4/HIV recombinants are potential new vaccine candidates for HIV.